Investigating of dual-jet air curtains for a landing gear noise reduction technology - Zhao, Kun (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
As the popularity of air travel increases, noise that it causes to the communities around airports has become a major concern to the aeronautical industry. World leading economic entities, such as EU and US, have made aircraft noise reduction an important section in their blueprint for aviation development. Airframe noise, generated by unsteady flow over the landing gear and high lift devices is of the prime interest due to its large contribution to the overall aircraft noise output. Thus, landing gear noise, the main source of airframe noise during take-off and approach when the engine operates at a low thrust, has been widely investigated. Some technologies have been proposed to reduce its noise emission, e.g. fairings and wheel hub caps. The prevailing fundamental idea behind these technologies is to cover the non-aerodynamic elements, thereby reducing the turbulent interaction. However, even these rudimentary add-ons may impede the inspection, maintenance and brake cooling of the landing gear, in addition to adding to the structural complexity and weight. The above mentioned technologies suggest incremental improvements to the reduction of landing gear noise. However, similar to the step-change innovative technologies in aeroengine design that have significantly reduced overall aircraft noise, innovation in low noise landing gear design is now required to help meet future environmental noise targets. The air curtain, also referred to as the planar jet, is proposed as a disruptive breakthrough technology to be installed upstream to the landing gear. It aims to deflect the incoming flow, shielding the bluff body so as to reduce the flow-induced noise. A preliminary study in 2009 validated its usefulness for aerodynamic noise reduction. However, it is also found that the emission of the air curtain self-noise introduced a limiting factor that impairs the performance of this technology, which can hinder the ultimate implementation. As such, this thesis investigates an alternative novel dual-jet configuration to minimise the air curtain self-noise emission. More specifically, in addition to the primary jet, a second jet is situated upstream of it, at a lower velocity, which reduces the total noise by both allowing the primary jet to operate at a lower velocity for the same shielding height and also by reducing the slot edge-exit noise due to allowing the primary jet to issue at 90 degrees. A main objective of this study is to validate and improve the performance of dual air curtains on the flow-induced noise reduction. Using tandem rods as a generic bluff body, this work first involves an approach to optimize the configuration of the air curtain application. In this study, the approach was proposed and utilised based on CFD simulations and PIV experiments. With the optimized configuration, both single jet and dual jet geometries were able to achieve substantial noise reduction. In particular, due to increased shielding of the bluff body, the introduction of the extra jet improved the total noise reduction when compared to the single jet. However, the suppression of primary jet noise was found to be less obvious than expected as the sound pressure level at some high frequency ranges was found to increase compared to the single jet. Thus, an optimal configuration of the dual jet geometry was proposed and tested, which requires less velocity from both jets for the same shielding height to the bluff body. The configuration was validated to be able to maximise the noise reduction with much less production of the jet self-noise. This study also discusses the flow regime of dual planar jets in the crossflow from the perspective of the fluid mechanics, which provides a good theoretical foundation for the implementation of the air curtain technology. Firstly, a novel approach to defining the jet leeward edge was developed based on a series of PIV experiments. Furthermore, based on CFD results, the recirculation structures of the flow regime and the development of the dual jets were characterised. In addition, this study preliminarily discusses the possibility of the combined use of dual air curtains with other technologies, using perforated fairings as an example. This work experimentally compares the individual use of dual air curtains with the perforated fairing, after which the combined use was tested. As a conclusion a recommendation was made, which accounts for not only acoustic performance but also engineering implementation. As a proof-of-concept, work in this study can contribute to the final realisation of the dual air curtains technology.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin